Credible privatization and market sentiment: Evidence from emerging bond markets - Boubakri, Narjess; Cosset, Jean-Claude; Smaoui, Houcem (Journal of International Business Studies, 2009)
This paper investigates the link between privatization and emerging market sovereign bond spreads. We conjecture that the way privatization is implemented may help to build a favorable market sentiment by gradually building investor confidence, which should then lead to a lower required compensation for policy risk. Controlling for other determinants of sovereign bond spreads, we find that privatization proceeds do not affect spreads, while privatization progress and share issues reduce spreads.